LD and Haplotype Block Analysis of SNPs on CAST Gene in Boerka Goat - Maharani, Dyah; Antonius, Antonius; Ginting, Simon P.; Elieser, Simon; Tarigan, A.; Budisatria, I Gede Suparta; Batubara, Aron; Hariyono, Dwi Nur Happy; Sari, Apriliana (2019)
The pattern of linkage disequilibrium (LD) in genome is a powerful signal in the association gene study. Calpastatin (CAST) gene plays a pivotal role in encoding meat quality (tenderization). In order to define the SNPs, twenty one of Boerka (Boer x Kacang) goats reared under control condition in Goat Research Institute, were used for blood sample collection. Five single nucleotide polymorphisms (SNPs) of CAST gene located in chromosome 7 were found using direct sequencing. The SNPs are namely g.146C>A (SNP- 1), g.224A>G (SNP-2), g.281G>A (SNP-3), g.373C>T (SNP-4) and g.431G>A (SNP-5). Those SNPs were analysed for LD and haplotype block analysis using haploview software. Four types of haplotype block have been performed to indicate the D’prime, LD, r-square (r2) and haplotype frequency. As a result, all block had high D’prime (=1.0). Each block had different SNPs combination. Block A, B, C and D formed 10, 3, 2 and 1 SNPs combination, respectively. The highest LD (1.75) and r2 (1.00) shown in block A with SNP1&2, SNP1&5, SNP2&5 combinations. The highest (97.6%) haplotype frequencies are defined in combination CA, CG and AG haplotypes located in SNP1&2, SNP1&5, SNP2&5, respectively. The lowest LD (0.01) and r2 (0.0010) found in SNP1&4, SNP2&4 and SNP4&5 combinations. In block B, three types of SNPs combination were made and indicated having medium of haplotype frequency (57.1%). For block C and D, two and one SNP combination were observed with similar haplotype frequency (57.1%). In conclusion, these information of LD and characterization of haplotype block structure may be useful parameter for guiding the CAST gene association study with economic traits especially for meat quality in Boerka goat population in the future study.